Pengaruh Kualitas Layanan, Harga, dan Promosi Terhadap Keputusan Pembelian Memilih Agen Travel pada PT. Asafa Global Wisata - Amal, Muh. Ihsanul; Latief, Baharuddin; Aksan, Muhammad; Mahmud, Amir; Kalla, Rastina (PT Maju Malaqbi Makkarana, 2025)
This study was conducted with the aim of: (1) To determine the partial effect of service quality, price, and promotion on Customer Decisions to choose PT. Asafa Global Wisata travel agents. (2) To determine the simultaneous effect of service quality, price, and promotion on Customer Decisions to choose PT. Asafa Global Wisata travel agents. This study uses primary data by distributing questionnaires to 114 customers as samples from PT. Asafa Global Wisata travel reports from August 2023 to June 2024 as many as 159 people, data collection was carried out from February to March 2025. Data were analyzed using Multiple Linear Regression analysis with the help of the SPSS Program. The results of the study show that (1) partially service quality, price, and promotion have a positive and significant effect on Customer Decisions to choose PT. Asafa Global Wisata travel agents (2) simultaneously service quality, price, and promotion have a positive and significant effect on Customer Decisions to choose PT. Asafa Global Wisata travel agents. This shows that with the implementation of increasingly better and continuously improved service quality, prices, and promotions, it will make prospective customers decide to choose PT. Asafa Global Wisata as their travel agent.